Muscle mass determined from urinary creatinine excretion rate, and muscle performance in renal transplant recipients. Issue 3 (25th March 2019) - Stam, Suzanne P.; Eisenga, Michele F.; Gomes‐Neto, Antonio W.; van Londen, Marco; de Meijer, Vincent E.; van Beek, André P.; Gansevoort, Ron T.; Bakker, Stephan J.L.
Abstract: Background: Muscle mass, as determined from 24‐h urinary creatinine excretion rate (CER), is an independent predictor for mortality and graft failure in renal transplant recipients (RTR). It is currently unknown whether CER is comparable with healthy controls after transplantation and whether it reflects muscle performance besides muscle mass. We aimed to compare urinary CER and muscle performance between RTR and healthy controls and to investigate whether urinary CER is associated with muscle performance in RTR. Methods: We included RTR, transplanted between 1975 and 2016 in the University Medical Center Groningen. Healthy controls were subjects screened for kidney donation. CER was calculated from a 24‐h urine collection. Muscle performance was assessed by handgrip strength, sit‐to‐stand test, and 2‐min walk test. Statistical analyses were performed using linear regression analyses. Results: We included 184 RTR (mean age 56.9 ± 11.9 years, 54% male recipient) and 78 healthy controls (age 57.9 ± 9.9, 47% male recipient). RTR were at a median time of 4.0 (1.1–8.8) years after transplantation. Mean CER was lower in RTR compared to healthy controls (11.7 ± 4.0 vs. 13.1 ± 5.2 mmol/24 h; P = 0.04). Significantly poorer results in muscle performance were found in RTR compared to controls for the handgrip strength (30.5 [23.7–41.1] N vs. 38.3 [29.3–46.0] N, P < 0.001) and the 2‐min walk test (151.5 ± 49.2 m vs. 172.3 ± 12.2 m, P < 0.001) but not for the sit‐to‐stand (12.2 ± 3.3 m vs. 11.9 ± 2.8 m, P = 0.46). In RTR, CER was significantly associated with handgrip strength (std. β 0.33; P < 0.001), independent of adjustment for potential confounders. In RTR, CER was neither associated with the time used for the sit‐to‐stand test (std. β −0.09; P = 0.27) nor with the distance covered during the 2‐min walk test (std. β 0.07; P = 0.40). Conclusions: Muscle mass as measured by CER in RTR is lower compared to controls. CER is positively associated with muscle performance in RTR. The results demonstrate that CER does not only reflect muscle mass but also muscle performance in this patient setting. Determination of CER could be an interesting addition to the imaging technique armamentarium available and applied for evaluation of muscle mass in clinical intervention studies and observational studies.